2021
DOI: 10.1186/s12870-021-03385-9
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal auxin distribution in Arabidopsis tissues is regulated by anabolic and catabolic reactions under long-term ammonium stress

Abstract: Background The plant hormone auxin is a major coordinator of plant growth and development in response to diverse environmental signals, including nutritional conditions. Sole ammonium (NH4+) nutrition is one of the unique growth-suppressing conditions for plants. Therefore, the quest to understand NH4+-mediated developmental defects led us to analyze auxin metabolism. Results Indole-3-acetic acid (IAA), the most predominant natural auxin, accumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…In the taproot grown in (NH4)2SO4, the nutrient and metabolic imbalance induced by ammonium was partially overcome by the increase of auxin level. Dziewit et al [55] studied the temporal and spatial distribution of auxin in Arabidopsis thaliana under long-term ammonium toxicity and found that auxin accumulated in leaves and roots, but not in root tips. The apparent auxin pattern in tissues is associated with the developmental adaptation of ammonium-growing plants with short branches and highly branched roots.…”
Section: Auxin and Cytokinin Might Regulate The Growth And Architectu...mentioning
confidence: 99%
“…In the taproot grown in (NH4)2SO4, the nutrient and metabolic imbalance induced by ammonium was partially overcome by the increase of auxin level. Dziewit et al [55] studied the temporal and spatial distribution of auxin in Arabidopsis thaliana under long-term ammonium toxicity and found that auxin accumulated in leaves and roots, but not in root tips. The apparent auxin pattern in tissues is associated with the developmental adaptation of ammonium-growing plants with short branches and highly branched roots.…”
Section: Auxin and Cytokinin Might Regulate The Growth And Architectu...mentioning
confidence: 99%
“…, growth inhibition at high concentrations and plant stimulation at low concentrations. This process is regulated by its biosynthesis, degradation, conjugation, and transport . IAA can also be formed from tryptophol by two subsequent oxidation steps .…”
Section: Introductionmentioning
confidence: 99%
“…This process is regulated by its biosynthesis, 4 degradation, 6 conjugation, 7 and transport. 8 IAA can also be formed from tryptophol by two subsequent oxidation steps. 4 Tryptophol glycosides, e.g., glucosides, galactosides, and arabinosides, often serve as a reservoir of IAA to keep the auxin balance in vascular plants.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The compounds indole-3-acetic acid (IAA), 1H-indole-3-butanoic acid (IBA), 1-naphthalene-acetic acid (NAA), 2-naphthoxy-acetic acid (BNOA), 2,4-dichlorophenoxyacetic acid (2,4-D), 4-chloro-phenoxyacetic acid (4-CP), and 4-iodophenoxyacetic acid (4-iodo pyridine) are collectively termed auxins [ 4 ]. Indoleacetic acid was the first plant hormone to be discovered and is mainly distributed in actively growing tissues, such as stem meristems, leaf primordia, young leaves, developing fruit and seeds, and pollen grains [ 5 ]. Auxins promote the formation of lateral roots and adventitious roots, adjust flowering and sex differentiation, regulate fruit set and development, and control apical dominance [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%